Associations between concussion and more severe TBIs, mild cognitive impairment, and early-onset dementia among military retirees over 40 years - Belding, Jennifer N.; Bonkowski, James; Englert, Robyn; Grimes Stanfill, Ansley; Tsao, Jack W. (Frontiers in Neurology, 2024)
Background and objectives As the population of U.S. service members (SMs) who have sustained concussions and more severe traumatic brain injuries (TBIs) during military service ages, understanding the long-term outcomes associated with such injuries will provide critical information that may promote long-term assessment, support, and rehabilitation following military service. The objective of this research was to examine whether concussion and more severe TBIs are associated with greater risk of precursors to dementia (i.e., mild cognitive impairment, memory loss), early-onset dementia, and any dementia. Methods This study used a retrospective cohort design wherein archival medical and career records from 1980 to 2020 identified U.S. military personnel who retired from military service and their corresponding Tricare-reimbursable medical encounters in inpatient and/or outpatient settings in military treatment facilities and/or purchased care settings both before and after retirement. All military personnel who served on active duty between 1980 and 2020 and were at least 45 years of age by 2020 were eligible for inclusion (N = 6,092,432). Those who were discharged from military service with a retirement designation, and were thus eligible for Tricare for Life, were included in the analytic sample (N = 1,211,972). Diagnoses of concussion and more severe TBI during active duty service recorded in inpatient settings between 1980 and 2020 and in outpatient settings from 2001 to 2020 were identified. Focal outcomes of interest included memory loss, mild cognitive impairment, Alzheimer’s, Lewy Body dementia, frontotemporal dementia, and vascular dementia. Dementia diagnoses before age 65 were labeled early-onset. Results Those with (vs. without) concussion diagnoses during military service were significantly more likely to be diagnosed with memory loss and mild cognitive impairment and any of the dementias examined. However, they were not at greater risk of being diagnosed with early-onset dementia. Discussion Military SMs diagnosed with concussion may be at elevated risk for long-term neurodegenerative outcomes including memory loss, mild cognitive impairment, and dementia. As the population of SMs who sustained TBI during the Global War on Terror continue to age, the prevalence of dementia will increase and may bring a unique burden to the VHA.